(untitled) (Journal of Human Sciences, 2021)
The aim of the current research is to identify the relationship between post-traumatic stress disorder and a sense of psychological unity among a sample of children displaced from Murzuq city, and to know whether there are statistically significant differences between post-traumatic stress disorder and a feeling of psychological unity, according to the two variables (gender and educational level) for the child). The researcher prepared a questionnaire for post-traumatic stress disorder and took into consideration that it is appropriate for their age and perception, and a measure of feelings of psychological loneliness prepared by Ibrahim kashkosh 1988, and the sample included (15) male child and (15) female child, and the results resulted in a strong correlation between pressure disorder post-traumatic stress, and the feeling of psychological loneliness among children displaced from Murzuq city, and presence of statistically significant differences between post-traumatic stress disorder, and the feeling of psychological loneliness, according to the gender variable in favour of females, and presence of statistically significant differences according to the variable of the educational level in favour of the seventh grade pupils.